IMPROVING STUDENTS' LEARNING OUTCOMES USING THE TARL APPROACH ASSISTED BY INTERACTIVE QUIZ IN THE SCIENCE SUBJECT OF GRADE V AT STATE ELEMENTARY SCHOOL 1 PALEMBANG - Diva, Karen; Hiltrimartin, Cecil; Manulang, Lilis Sri Jayanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2025)
This study aims to improve learning outcomes using the interactive quiz-assisted tarl approach (snakes and ladders) in the subject of science. This study is a Classroom Action Research. The study was conducted at SD Negeri 1 Palembang, with 27 students consisting of 14 male students and 13 female students. Learning was carried out using the Teaching at The Right Level approach assisted by interactive quizzes (snakes and ladders). Data were analyzed descriptively and presented in the form of tables and graphs. The results of the study on pre-cycle activities, cycle 1, and cycle 2 obtained scores of 55, 60, and 78. In the implementation of the pre-cycle, cycle 1, and cycle 2, the percentages were 45%, 55%, and 85%. Given the determination of the indicator of success of student learning outcomes of 75% has reached a value of N> 75. Based on these results, the research conducted on science learning using the Teaching at the Right Level approach assisted by interactive quizzes (snakes and ladders) in the VC class of elementary schools can be declared successful and can improve student learning outcomes.